Drengeværelset på spil. Moralsk panik og æstetisk selvskabelse - Klitgaard Povlsen, Karen (Aktualitet - Litteratur, kultur og medier, 2021)
In early Birmingham School cultural studies, boys were on the streets, girls were in their rooms. Today,Danish middle-class children are more often than not in their rooms playing online games. The Danish boys have the European record in playing computer games at home in their rooms. Should we be concerned? Or are the boys socially active alone in the room? This article presents a small preliminary case study with three Danish boys of different ages, followed over some months either virtually or in real life during the corona-pandemics.